Purification, crystallization and preliminary X-ray diffraction data of UDP-galactopyranose mutase from Aspergillus fumigatus - Penman, George A. (International Union of Crystallography, 2012)

(untitled)
Aspergillus fumigatus UDP-galactopyranose mutase (AfUGM) is a potential drug target involved in the synthesis of the cell wall of this fungal pathogen. AfUGM was recombinantly produced in Escherichia coli, purified and crystallized by the sitting-drop method, producing orthorhombic crystals that diffracted to a resolution of 3.25 Å. The crystals contained four molecules per asymmetric unit and belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 127.72, b = 134.30, c = 173.84 Å. Incorporation of selenomethionine was achieved, but the resulting crystals did not allow solution of the phase problem.